2020
DOI: 10.1007/s10566-019-09542-4
|View full text |Cite
|
Sign up to set email alerts
|

What do ADHD Neuroimaging Studies Reveal for Teachers, Teacher Educators and Inclusive Education?

Abstract: Background: Ongoing debate about Attention Deficit Hyperactivity Disorder (ADHD) has not resolved ambivalent teacher beliefs about ADHD. This is an important matter since teachers' beliefs influence their pedagogy, classroom management, and their referral procedures for formal diagnoses of ADHD. They therefore must be provided with up-to-date professional learning about ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 197 publications
(155 reference statements)
0
9
0
Order By: Relevance
“…An individual with ADHD may present with hyperactive symptoms (e.g., has difficulty sitting still, difficulty managing impulses), inattentive symptoms (e.g., often does not seem to listen when spoken to directly, often losing track of time or possessions), or a combination of both (APA, 2013). Advances in neuroscience have demonstrated that there are distinct differences in neural anatomy and neural processing among children with ADHD compared to typically developing children (Boon, 2020;Kasparek et al, 2015;Uddin et al, 2017). Scuitto et al (2000) found that while teachers may know the signs and symptoms of ADHD, they are less versed in the course and treatment of ADHD.…”
Section: Pay Attention To This: a Knowledge Translation Study Of Adhd And Its Brain Basis To Preservice And In-service Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…An individual with ADHD may present with hyperactive symptoms (e.g., has difficulty sitting still, difficulty managing impulses), inattentive symptoms (e.g., often does not seem to listen when spoken to directly, often losing track of time or possessions), or a combination of both (APA, 2013). Advances in neuroscience have demonstrated that there are distinct differences in neural anatomy and neural processing among children with ADHD compared to typically developing children (Boon, 2020;Kasparek et al, 2015;Uddin et al, 2017). Scuitto et al (2000) found that while teachers may know the signs and symptoms of ADHD, they are less versed in the course and treatment of ADHD.…”
Section: Pay Attention To This: a Knowledge Translation Study Of Adhd And Its Brain Basis To Preservice And In-service Teachersmentioning
confidence: 99%
“…Children with ADHD face barriers that their peers do not, such as a lack of adequate support in transition periods (e.g., from elementary to secondary school, from high school to postsecondary) as well as lower parental expectations; in fact, the latter is so impactful, it has been shown to explain the differences between post-secondary education attendance between students with ADHD and other youth (Statistics Canada, 2019). Boon (2020) has advocated for a systematic update in the professional development for preservice and in-service teachers to better support students with ADHD. Specifically, Boon (2020) suggested that an understanding of the neuroscience of ADHD will enhance understanding of students with ADHD and why they behave differently than other students.…”
Section: Pay Attention To This: a Knowledge Translation Study Of Adhd And Its Brain Basis To Preservice And In-service Teachersmentioning
confidence: 99%
“…There are review studies in the field which examine issues such as research regarding teacher training for IE [37], initial teacher education for inclusion [38], research findings on ADHD with relevance for teachers, teacher educators and IE [39], the use of augmented reality in IE [40], pre-service teachers' attitudes towards inclusion [41], inclusive pedagogy in physical education [42], and teacher training programs for the inclusion of students with special education needs in regular primary schools [43]. Review studies are valuable in providing experts' evaluation on the literature in a field, but as an alternative approach, bibliometric studies are objective and reliable resources that offer a mapping of a research field, allowing for a much wider coverage of selected studies [31].…”
Section: Literature Analysismentioning
confidence: 99%
“…Boon (2020) has advocated for a systematic update in the professional development for preservice and in-service teachers to better support students with ADHD. Specifically, Boon (2020) suggested that an understanding of the neuroscience of ADHD will enhance understanding of students with ADHD and why they behave differently than other students. In this present study, in turn, we developed a knowledge translation (KT) activity aimed at increasing teacher knowledge of the brain basis of ADHD, in order to respond to the needs of students with ADHD and help teachers reflect on what is needed to provide this support.…”
Section: Pay Attention To This: a Knowledge Translation Study Of Adhd And Its Brain Basis To Preservice And In-service Teachersmentioning
confidence: 99%
“…Teachers are often ambivalent and unconvinced about the legitimacy of ADHD diagnoses and the brain basis of ADHD (Boon, 2020). Evidence shows that teachers with more knowledge of ADHD in general (symptoms, diagnosis, treatment) display less stigma towards students with ADHD (Toye et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%